Utilization of a Combination of Rice Husk and Silica Sand as an Adsorbent for Palm Oil Mill Effluent - Whywhen, Whywhen; Harimu, La; Mulyana, Wa Ode (Indonesian Journal of Science and Pharmacy, 2026)
Palm Oil Mill Effluent (POME) is one of the main wastes generated from the palm oil industry, characterized by high organic content and significant potential to pollute the environment. This study aims to determine the effectiveness of a combination of rice husk ash and silica sand as adsorbents in reducing COD, BOD, and TSS levels, as well as stabilizing the pH of POME, and to evaluate changes in the physical characteristics of the wastewater after the adsorption process. The method used in this study was column adsorption. The evaluation included pH, COD, BOD, and TSS analyses, as well as organoleptic tests covering color, odor, and turbidity. The results showed that the pH increased from 3.3 to 6.3 with an efficiency of 90.90% and met the required quality standards. COD decreased from 660 mg/L to 40 mg/L (88.88%), BOD from 18 mg/L to 2 mg/L (93.93%), and TSS from 1,050 mg/L to 130 mg/L (87.61%). Organoleptic test results indicated an improvement in wastewater quality, as shown by the color change from brown to clearer/grayish, reduced odor intensity, and decreased turbidity. Based on these findings, the combination of rice husk ash and silica sand is effective as an economical and efficient adsorbent in improving POME quality in accordance with environmental standards.